Synthesis of 1H-Isochromenes and 1,2-Dihydroisoquinolines by Indium(III)-Catalyzed Cycloisomerization of ortho-(Alkynyl)benzyl Derivatives - Seoane-Carabel, Fabio; Alonso-Marañón, Lorena; Sarandeses, Luis A.; Sestelo, José Pérez (Synthesis, 2022)
1H-Isochromenes and 1,2-dihydroisoquinolines are synthesized by regioselective indium(III)-catalyzed intramolecular hydrofunctionalization of o-(alkynyl)benzyl derivatives. The reaction with o-(alkynyl)benzyl alcohols and amines proceeds using indium triiodide (5–10 mol%) in toluene at 80–100 °C via regioselective 6-endo-dig intramolecular alkyne hydroalkoxylation or hydroamination in good yields. Alternatively, the cycloisomerization reaction of o-(alkynyl)benzaldehydes and imine derivatives using InI3 (5 mol%) and the Hantzsch ester (120 mol%) takes place, under milder reaction conditions, to give a variety of functionalized 1H-isochromenes and 1,2-dihydroisoquinolines through a domino cycloisomerization/reduction approach.
Keywords: homogeneous catalysis; indium catalysis; cycloisomerization; alkynes; π-acid catalysis